1204. The Effect of Coinfection with Babesiosis and Lyme Disease on Novel Biomarkers. (31st December 2020) - Lum, Michael D; Reardon, Kelsey; Spector, Rachel; Garry, Evan; Papamanoli, Aikaterini; Marcos, Luis
Abstract: Background: Current literature presents conflicting results regarding the clinical manifestations of coinfection with Babesia microti (Babesiosis) and Borrelia burgdorferi (Lyme disease). The aim of this study is to investigate the effect that coinfection with Babesiosis and Lyme Disease has on standard and novel biomarkers markers such as C-reactive protein (CRP), erythrocyte sedimentation rate (ESR) and procalcitonin (Pc), which may assist in elucidating how these pathogens interact within human hosts. Methods: Babesia cases were collected from Stony Brook University Hospital from 2012 to 2019. Cases of Babesia were included if parasites were detected by peripheral blood smear and confirmed by PCR. Lyme disease diagnosis criteria involved 2-tier testing per CDC guidelines. Cases were divided into three cohorts based on if they had CRP, ESR or Pc tested. Cohorts were divided into two groups: Babesiosis alone vs coinfection with Lyme Disease. Median values were analyzed for the following biomarkers across both groups: parasitemia, hemoglobin (Hgb), white blood cells (WBC), platelets, indirect bilirubin (IB), lactate dehydrogenase, ESR, CRP and Pc. Fisher Exact and Wilcoxon Rank sum tests were used and P values < 0.05 were considered statistically significant. Results: ESR values trended higher in monoinfection compared to coinfection (50 vs 36 mm/hr, p=0.63). Within this cohort, the coinfection group had significantly lower platelet values compared to monoinfection (52 vs. 75.5 K/uL, p=0.04, Table 1). Within the CRP and Pc cohorts, monoinfection had higher trends of parasitemia compared to coinfection (CRP group: 1.6 vs 0.7%, p=0.14, Pc group: 1.4 vs 0.7% p=1.0, Table 2&3). Pc levels were similar in both groups (1.1 vs 1.2 ng/mL, p=1.0, Table 3). Table 1: Demographics and Biomarkers for Patients with Babesiosis Monoinfection vs. Coinfection with Babesiosis and Lyme Disease that had ESR Measured. Table 2: Demographics and Biomarkers for Patients with Babesiosis Monoinfection vs. Coinfection with Babesiosis and Lyme Disease that had CRP Measured. Table 3: Demographics and Biomarkers for Patients with Babesiosis Alone vs Coinfection with Babesiosis and Lyme Disease that had Procalcitonin Measured. Conclusion: Coinfection had significantly lower platelets within the ESR cohort but not in other cohorts. While not statistically significant, monoinfection showed greater trends of ESR and parasitemia, which is consistent with previous studies that suggest that B. burgdorferi may mitigate the effects of B. microti infection. CRP and Pc levels were similar across both groups suggesting that the utility of using novel biomarkers to elucidate the interaction between B. burgdorferi and B. microti during simultaneous infection requires further study. Disclosures: All Authors : No reported disclosures